2021
DOI: 10.24815/siele.v8i1.17608
|View full text |Cite
|
Sign up to set email alerts
|

Language use, language attitude, and identity: Perceptions of high school students attending an international school in Jakarta

Abstract: This study explores the perceptions of high school students who attend an international school in Jakarta towards language use, language attitude, and identity. One hundred sixty-five students aged between 15-18 years old participated in this study. They were divided into three categories based on their nationalities, namely (1) Indonesian students who were born and raised in Indonesia, (2) Indonesian students who were born and raised outside Indonesia, and (3) non-Indonesian students (expatriates) who were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Duolingo can be a great supplement to these activities, but it should not be relied on as the sole source of language practice. This aligns with Kroon and Kurvers (2020) and Sukamto et al (2021) that language practice can maintain language attitude. In this case, human language is still needed to be empowered.…”
Section: Excerpt 11supporting
confidence: 76%
“…Duolingo can be a great supplement to these activities, but it should not be relied on as the sole source of language practice. This aligns with Kroon and Kurvers (2020) and Sukamto et al (2021) that language practice can maintain language attitude. In this case, human language is still needed to be empowered.…”
Section: Excerpt 11supporting
confidence: 76%
“…This is contradictory to some studies in international schools. For example, Sukamto et al (2021) described a different situation in an international school in Jakarta where local students needed to learn the English language to be able to participate in lessons, and to communicate and socialise with friends in school. In our study we observed that the social dimension of the use of the Greek language affects the cultural–cognitive pillar of the researched schools (Bunnell et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the official language used in ASEAN activities is English (Kirkpatrick, 2012a;Shobikah, 2017). English is also the subject that is introduced in the world of education in schools in the ASEAN region (Kam, 2002;Kirkpatrick, 2012b, Kirkpatrick & Liddicoat, 2017Sukamto, et al, 2021;Damanik, 2022). English in South East Asia region is seen as a means of embracing globalization and a medium of seizing international politics, economics, education, and trade opportunities (Diyati & Madya, 2021).…”
Section: Introductionmentioning
confidence: 99%